If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + 26 = 2(x + 1) Combine like terms: -16 + 26 = 10 10 = 2(x + 1) Reorder the terms: 10 = 2(1 + x) 10 = (1 * 2 + x * 2) 10 = (2 + 2x) Solving 10 = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + -2x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 10 + -2x = 2 + 0 10 + -2x = 2 Add '-10' to each side of the equation. 10 + -10 + -2x = 2 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = 2 + -10 -2x = 2 + -10 Combine like terms: 2 + -10 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| .75x+3=x+.5 | | 6/3x-5=3/2x | | 2(x-10)=-8 | | 0.09xX=83.07 | | (-4±√20)/2 | | -9-2x+6x=27 | | 37x+7=6(6x+1) | | 18x-7=14x-23 | | 2x+23y=11 | | y+1.2=2 | | 9x+1.5y=11 | | x+56=-24 | | -10z-0.9=-20z+1.1 | | -9+2+3x=22 | | 2(2x+2)+2(x+34)=312 | | 2x^2+30x+189=0 | | f(n)=9/n | | X/10-x/35=1/10 | | -5.39=logx | | 7x+2=5x+3 | | 6(79-5x)=11(4x-4) | | 180-x=.4(x)+5 | | 2(x+3)=8x-33 | | Y=10x^3+6 | | 13x-8y=-711 | | 8+2=-5(4x+2) | | 4(3x+9)=-32+44 | | 4(5x-2)=18 | | 2y=-8xy | | 13x-936=12x-624 | | 8xy=-2y | | y^2+3y=40 |